A Study on Learning Pre-Algebra Using Interactive Multimedia Courseware Within Collaborative Learning Set-Up and E-Mail Interactions - Mohd Sazali Khalid; Sulaiman Yamin; Sri Adelila Sari (Graduate Program of Syiah Kuala University, 2012)
Abstract – Many students at diploma level are weak in mathematics even after spending eleven years in Malaysian education system. However, throughout the world there are research studies been done with mixed results using technology and collaborative learning. The objective of this paper is to analyze the effect of learning pre-algebra using interactive courseware with collaborative learning by using STAD set ups with interactive courseware using e-mail facilities during team discussion only. Quasi experimental type research was used. The gain score (differences between post and pre test) between the two equivalent groups were obtained. Diploma Information Technology first year students in two different intake years 2009 and 2010 in UTHM were employed. ‘t-test’ results revealed the second group using e-mail is statistically significantly inferior to the group using purely interactive multimedia courseware CDiCL only with STAD team discussion. On average participants experienced higher gain scores in the first group (Mean = 3.28, SE=0.433), than participants in the second group (M=0.77, SE=0.354). This difference was statistically significant (t (74) = 4.51, p